Impacts of real-time feedback on driving behaviour: a casestudy of bus passenger drivers - Rolim, Catarina; Baptista, Patrícia; Duarte, Gonçalo; Farias, Tiago; Pereira, João (European Journal of Transport and Infrastructure Research, 2017)
Over the years, there has been an increase in the focus on driving behaviour as a solution to minimize the road transportation high levels of energy consumption, as well as the emission of pollutants. The aim of this study was to analyse the impacts of real-time feedback on the driving behaviour of bus drivers, and to assess the potential impact of the characteristics of these subjects (age and time working at the company) on such behaviour. Data was collected with an on-board device installed in buses of a Portuguese urban transport operator. Three monitoring periods were considered: an initial phase, in which real-time feedback was given to drivers (phase 1), followed by a period of no feedback (phase 2), and then a final stage in which feedback was resumed (phase 3). A repeated measures analysis of variance was performed to assess the impacts of feedback in several driving indicators across the aforementioned phases. The results revealed that bus drivers accrue benefits from the feedback received, with significant differences between the three monitoring periods for all driving indicators analysed. After suspending the feedback, increases between 6% and 55% of the incidence of undesired driving indicators were observed, mainly in extreme brakes, extreme accelerations, excess RPM, and hard stops. Such insights can provide bus operators with new tools to develop programs promoting efficient driving behaviours.